Association of Immune and Metabolic Receptors C5aR and C5L2 with Adiposity in Women. (12th January 2014) - Poursharifi, Pegah; Rezvani, Reza; Gupta, Abhishek; Lapointe, Marc; Marceau, Picard; Tchernof, André; Cianflone, Katherine
Abstract : Adipose tissue receptors C5aR and C5L2 and their heterodimerization/functionality and interaction with ligands C5a and acylation stimulating protein (ASP) have been evaluated in cell and rodent studies. Their contribution to obesity factors in humans remains unclear. We hypothesized that C5a receptors, classically required for host defense, are also associated with adiposity. Anthropometry and fasting blood parameters were measured in 136 women divided by body mass index (BMI): normal/overweight (≤30 kg/m 2 ; n = 34), obese I (≤45 kg/m 2 ; n = 33), obese II (≤51 kg/m 2 ; n = 33), and obese III (≤80 kg/m 2 ; n = 36). Subcutaneous and omental adipose tissue C5aR and C5L2 expression were analysed. C5L2 expression was comparable between subcutaneous and omental across all BMI groups. Plasma ASP and ASP/omental C5L2 expression increased with BMI ( P < 0.001 and P < 0.01, resp.). While plasma C5a was unchanged, C5aR expression decreased with increasing BMI in subcutaneous and omental tissues ( P < 0.01 and P < 0.05, resp.), with subcutaneous omental depots. Omental C5L2/C5aR ratio increased with BMI ( P < 0.01) with correlations between C5L2/C5aR and waist circumference, HDL-C, and adiponectin. Tissue and BMI differences in receptors and ligands, particularly in omental, suggest relationship to metabolic disturbances and highlight adipose-immune interactions.